Renewable Energy Discourse on Social Media: A Cross-Platform Sentiment Analysis - Hafize Nurgül Durmuş Şenyapar (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The global shift towards renewable energy has garnered significant attention in digital spaces, with platforms teeming with discourse about its implications, challenges, and potential. This study undertook a comprehensive exploration of this digital discourse across prominent social media platforms, including Quora, Facebook, Instagram, Reddit, and the platform formerly known as Twitter, now “X.” Leveraging the API-based tool from BrandMentions, a dataset focused on the keyword “Renewable Energy” was extracted and conducted in-depth sentiment and textual analyses. Findings revealed a predominant positive sentiment, accounting for 71.44% of the mentions. English emerged as the dominant language, comprising 97.48% of the dataset. Platform-specific insights showcased diverse aspects of the renewable energy conversation, from career-related inquiries on Quora to industry trends on Reddit. Co-occurrence analysis further underscored the multifaceted nature of discussions, highlighting areas of technological innovation, sustainability concerns, and commercial implications. This research sheds light on the complex web of online discourse on renewable energy, providing significant implications for stakeholders, policymakers, and researchers. Future studies might delve deeper into regional sentiments, and temporal shifts in discourse and employ more advanced analytical tools for granular insights.